Accuracy of PSA Self‐Reports among Low‐Income Men with Prostate Cancer after a Public Health Nursing Intervention. Issue 6 (8th May 2016) - Zavala, Mary Wassel; Yule, Arthur; Kwan, Lorna; Lambrechts, Sylvia; Maliski, Sally L.; Litwin, Mark S.
Abstract: Objectives: To examine accuracy of patient‐reported prostate‐specific antigen (PSA) levels among indigent, uninsured men in a state‐funded prostate cancer treatment program that provides case management, care coordination, and health education. Design and Sample: Program evaluation. About 114 men with matched self‐ and lab‐reported PSA levels at program enrollment and another time point within 18 months. Measures: Abstraction of self‐ and lab‐reported PSA levels to determine self‐report as "accurate" or "inaccurate, " and evaluate accuracy change over time, before and after nursing interventions. Chi‐square tests compared patients with accurate versus inaccurate PSA values. Nonlinear multivariate analyses explored trends in self‐reported accuracy over time. Intervention: Program enrollees receive prostate cancer education from a Nurse Case Manager (NCM), including significance of PSA levels. Men self‐report PSA results to their NCM following lab draws and appointments. The NCM provides ongoing education about PSA levels. Results: Of the sample, 46% ( n  = 53) accurately reported PSA levels. Accuracy of PSA self‐reports improved with increasing time since program enrollment. Compared with men at public facilities, those treated at private facilities showed increasing accuracy in self‐reported PSA ( p  = .038). Conclusion: A targeted nursing intervention may increase specific knowledge of PSA levels. Additionally, the provider/treatment setting significantly impacts a patient's disease education and knowledge.